2013
DOI: 10.1002/aic.14180
|View full text |Cite
|
Sign up to set email alerts
|

Granulation rate processes in the kneading elements of a twin screw granulator

Abstract: To characterize the granulation rate processes in the kneading section of the twin screw granulator, separate experiments were conducted using exclusively conveying elements as the baseline in addition to different configurations of kneading elements. The configuration parameters examined were the length of the kneading section, the advance angle, and the angle direction. Granule size, shape and liquid distribution were measured. Two main rate processes were observed (1) breakage and layering, and (2) Shear el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 28 publications
(47 reference statements)
6
56
1
Order By: Relevance
“…The kneading elements provide a shearintensive zone that allows granule formation by intimate mixing of liquid and powder. However, the granules obtained are characterized by a broad bimodal size distribution, with the presence of lumps and un-granulated fines (El Hagrasy et al, 2012;Kleinebudde, 2008, 2010;El Hagrasy and Litster, 2013;Dhenge et al, 2010Djuric et al, 2009;Melkebeke et al, 2008). A broad size distribution is undesirable in a wet granulation process due to potential issues with drying uniformity and powder segregation.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…The kneading elements provide a shearintensive zone that allows granule formation by intimate mixing of liquid and powder. However, the granules obtained are characterized by a broad bimodal size distribution, with the presence of lumps and un-granulated fines (El Hagrasy et al, 2012;Kleinebudde, 2008, 2010;El Hagrasy and Litster, 2013;Dhenge et al, 2010Djuric et al, 2009;Melkebeke et al, 2008). A broad size distribution is undesirable in a wet granulation process due to potential issues with drying uniformity and powder segregation.…”
Section: Introductionmentioning
confidence: 97%
“…The flexible equipment design introduces additional manipulated variables, including screw configuration, screw speed, and shaft length. Earlier research work has demonstrated that screw configuration has a strong impact on granule attributes Kleinebudde, 2008, 2010;El Hagrasy and Litster, 2013;Thompson and Sun, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent development of granulation technique can be seen (e.g. [2], [3], [4], [5], [6], [7], [8], [9], [10], [11])…”
Section: Introductionmentioning
confidence: 99%